PELATIHAN JUMANTIK NYAMUK DALAM RANGKA PENGENDALIAN VEKTOR DEMAM BERDARAH DENGUE PADA SISWA SEKOLAH DASAR - Damayanti, Putu Ayu Asri (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
Dengue Hemorrhagic Fever (DHF) vector control is a way to reduce dengue cases in Bali Province, which is still endemic for dengue fever. Eradicating mosquito nests can be done by killing mosquito larvae in breeding places inside and outside the house. Independent community participation is needed in eradicating Aedes aegypti mosquito larvae. The larva monitoring movement can be carried out by all levels of society, including children. In order for children to be able to monitor larvae in their environment, children must have knowledge of dengue fever and how to monitor and kill mosquito larvae. The aim of the activity is to increase knowledge of larva monitoring and how to eradicate it among students at SD Negeri 6 Delod Peken Tabanan. The implementation method is in the form of training activities by providing education accompanied by practical assignments accompanied by measuring knowledge before (pre-test) and after (post-test) training. The results were that the distribution of student answer data was not normal, (p=0.00). The median pre-test knowledge score was 4 (1-8) and post-test 8(1-10). There was a significant difference in students' knowledge scores before and after being given training (p= 0.00). It can be concluded that the training has proven effective in increasing students' knowledge at SD Negeri 6 Delod Peken. Periodic and sustainable knowledge increasing activities are needed among elementary school children to increase independent community participation in monitoring and eradicating mosquito larvae in an effort to help reduce dengue fever cases in Bali. Keywords: training, monitoring larvae, dengue hemorrhagic fever, elementary school students.